Get ready! High urgency reduces beta band cortico-muscular coherence during motor preparation - Marinovic, Welber; Boyd, Reon; Nguyen, An (2024)
Motor preparation is a dynamic process that is tuned to task demands such as urgency. This study examined the effect of urgency to move on cortico-muscular coherence (CMC) in the beta frequency band during motor preparation. Participants (n = 25) prepared for a rapid wrist flexion movement under two distinct scenarios: high (350 ms to prepare) and low (1400 ms to prepare) urgency. Before participants performed the ballistic actions, they were required to hold a light contraction of the flexor carpi radialis muscle for 3 s. During this holding time, we simultaneously obtained EEG and EMG signals to estimate their coherence —a measure of how much brain and muscle activity is synchronized at specific rhythms— over the last 1 s of the contraction interval. Contrary to our hypothesis, we found greater CMC in conditions of low urgency rather than high urgency. This finding suggests that participants prioritized attending to the visual stimuli, dividing their attention to capture the preparation go-signal, rather than preparing the motor system, leading to a reduction in CMC. This interpretation suggests a cognitive-motor trade-off, wherein attentional resources are allocated more to sensory processing that to motor preparedness in urgent situations.